Obraz Venički Erofeeva - Benčić, Živa (Array, 2002)
Considering that we can talk about caricature-like nature of a certain character only within a mimetic prose paradigm, then the character of Venichka Erofeev, with his deliberately stressed and visibly exaggerated faults such as faint-heartedness or drunkenness can be interpreted as a caricature of the author himself only if observed from the point of view of the author’s autobiographical rather than cultural memory. However, each time the center of attention moves to the poem’s intertextuality, the mimetic paradigm of the work is challenged, and the illusion of Venichka as an autobiographical hero or a caricature replica of the author himself tumbles down. If this complex postmodernist character is analyzed regarding its literary rather than real-life model, then we should talk about its parodic nature sooner than its caricature-like features. In the end the article aims to prove that the author as such is not the only authority responsible for the creation of the meaning, i.e. that not only the author’s subjective memory, (autobiographical as well as cultural) but also objective “genre memory” (Bakhtin) proved to be esthetically productive in the formation of the poem’s main character. It is precisely “genre memory” that places Venichka in the long tradition of antiheroes of the Russian literature; the tradition best represented by the antiheroes of Old-Russian parodies dating from the second half of the 17th century